LncRNA‐PCAT1 targeting miR‐145‐5p promotes TLR4‐associated osteogenic differentiation of adipose‐derived stem cells - Yu, Lingjia; Qu, Hao; Yu, Yifeng; Li, Wenjing; Zhao, Yu; Qiu, Guixing (Journal of cellular and molecular medicine, 2018)
This study was aimed to explore the differential expression of long noncoding RNAs (lncRNA)‐PCAT1, miR‐145‐5p and TLR4 in osteogenic differentiation via the Toll‐like receptor (TLR) signalling pathway and consequently determine the potential molecular mechanism. The mRNAs and pathways related to the osteogenic differentiation in human adipose‐derived stem cells (hADSCs) were analysed by bioinformatics. The MiRanda and TargetScan database were employed to detect the potential binding sites of miRNAs on lncRNAs and mRNAs. The differential expression of lncRNA‐PCAT1, miR‐145‐5p and TLR4 were detected by qRT‐PCR. Rrelated protein expression was analysed by Western blot. The targeted relationships between lncRNA‐PCAT1, miR‐145‐5p and TLR4 were verified by dual‐luciferase reporter assay. Alkaline phosphatase (ALP) activity and ARS staining assays were used to measure the impacts exerted by lncRNA PCAT1, miR‐145‐5p and TLR4 mRNA on osteogenic differentiation. After the induction of osteoblast differentiation, the expression of lncRNA‐PCAT1 and TLR4 increased, while the expression of miR‐145‐5p decreased. Dual‐luciferase reporter assay confirmed the targeted relationship between lncRNA‐PCAT1, miR‐145‐5p, and TLR4. LncRNA‐PCAT1 negatively regulated miR‐145‐5p and positively regulated TLR4. Knockdown of lncRNA‐PCAT1 or TLR4 decreased the expression of osteogenic differentiation‐related proteins, reduced the ALP and ARS levels and the activity of the TLR signalling pathway. MiR‐145‐5p could reverse the effects of PCAT1 and TLR4 in hADSCs osteogenic differentiation. LncRNA‐PCAT1 negatively regulated miR‐145‐5p, which promoted TLR4 expression to promote osteogenic differentiation by activating the TLR signalling pathway.